THE EFFECT OF USING RECIPROCAL TEACHING STRATEGY ON STUDENTS READING COMPREHENSION AT TENTH GRADE MECHANICAL ENGINEERING SMK N 1 SUMATERA BARAT - Armando Saiola; Rahma Dania; Suparmi (CV Swa Anugrah, 2023)
This study aimed to determine the effect of the reciprocal strategy on reading comprehension of mechanical engineering students at SMK N 1 West Sumatra. This research was a quantitative research with the type of pre-experimental research. Sampling data was collected using a random sampling technique. The number of research samples was 25 people with a population of 533 people. The treatment the researchers gave to the sample aimed to determine the effect of reading comprehension outcomes using a reciprocal teaching strategy. The instrument used in collecting data was a learning achievement test with multiple choice and essay types. Data analysis was carried out using Microsoft Excel. Based on the findings of the research that was conducted, it is observed that the t-test value of 33,32 exceeds the critical t-table value of 2.063 at a significance level of α = 0.05. This indicates a significant difference in students' reading comprehension abilities before and after implementing the reciprocal teaching strategy. This shows that the alternative hypothesis (H1) has been accepted, whereas the null hypothesis (Ho) has been rejected.